Fungicide application and host-resistance for potato late blight management: benefits assessment from on-farm studies in S.W. Uganda - Namanda, S.; Olanya, O.M.; Adipala, E.; Hakiza, J.J.; El-Bedewy, R.; Baghsarif, A.S.; Ewell, P. (Crop Protection, 2004)
Late blight caused by Phytophthora infestans, is one of the most significant constraints to potato production in Uganda and other regions of the world. Fungicides and host plant resistance are among the most efficient control options available to growers. Field trials were conducted in 1999 and 2000 in South-western Uganda to evaluate the cost effectiveness of fungicide application regimes on six potato varieties. A factorial experiment with five fungicide application intervals (weekly, fortnightly, IPM, no spray and farmers’ practice) and six potato varieties was established. Late blight infection was prevalent in both years, and a significant amount of disease was detected (P<0.05). Application of fungicide treatments considerably reduced late blight progress, with a corresponding increase in tuber yield. Based on monitoring of late blight disease occurrence and weather variables, two applications of the contact fungicide mancozeb on a moderately resistant variety was the most economical. Marginal rates of return and net benefits were significantly affected by fungicide applications. In the IPM treatment, late blight disease monitoring or scouting prior to first fungicide applications resulted in significant economic gains compared to scheduled applications of weekly and biweekly or no application (control) treatments.
Keywords: Mancozeb Dithane M45; Fungicide application; Economic returns; Host resistance; Late blight